Effects of concurrent administration of modified live viral vaccines with RB51 on immune responses to RB51 - Crawford, Lauren; Falkenberg, Shollie; Putz, Ellie Jordan; Olsen, Steven; Boggiatto, Paola M. (Frontiers in Veterinary Science, 2023)
Brucella abortus is a gram negative, zoonotic pathogen that can cause abortions and stillbirths in the cattle industry and has contributed to significant economic losses to cow-calf producers. Cell mediated immunity (CMI) is an important component of the immune response associated with protection against Brucella abortus and other intracellular pathogens. Brucellosis and viral modified live vaccines (vMLV) are licensed individually but may be used concurrently under field conditions. The goal of this study was to characterize immune responses to RB51 vaccination and determine the effect of concurrent vaccine administration. Peripheral blood mononuclear cells (PBMC) from non-vaccinated cattle and cattle vaccinated with either Brucella abortus strain RB51, a vMLV or both RB51 and a vMLV vaccine were isolated. The frequency of CD4+, CD8+ and γδ+ T cell populations within PBMC, and the frequency of interferon gamma (IFN-γ) production within these cell types was characterized via flow-cytometry. Although immune responses were greatest in PBMC from cattle vaccinated with only RB51, cattle vaccinated with both RB51 and vMLV demonstrated measurable T cell responses associated with protective immunity. Data suggests a lack of significant biological differences between the groups in protective immune responses. Collectively, our data demonstrated a lack of vaccine interference following concurrent administration of vMLV and RB51. Although concurrent administration of individually licensed vaccines may influence immune responses and contribute to vaccine interference, potential vaccine combinations should be evaluated for biological effects.